Psychological and emotional benefits of virtual reality-based exercise for postpartum women with lumbopelvic pain: A randomized controlled trial - Javeria Aslam; Alba Paris-Alemany; Carlos Romero-Morales; Raquel Díaz- Meco Conde (PLOS Global Public Health, 2026)
Women experiencing the postpartum stage often develop psychological distress, fear of movement, and maladaptive pain coping, which is a hindrance to healing lumbopelvic pain (LPP). Traditional exercise (TE) programs are usually characterized by low adherence. Virtual reality (VR) - based exercise can be a strong immersive experience, which can positively affect emotional well-being, decrease fear of pain, and increase coping mechanisms. To determine the level of effectiveness of VR-based exercise programs as compared to TE in enhancing psychological and emotional outcomes in postpartum women with LPP. 60 postpartum women aged 20–40 years with LPP, registered between 2–12 weeks post-delivery, were enrolled in a single blind randomized controlled trial. The project followed a simple randomization process and was conducted computationally with an equal distribution (1:1) between the VR and TE groups. Both of the groups were exposed to 8 sessions of pelvic floor muscle training over a month. The VR group additionally performed immersive tasks using Meta Quest 2 headsets and Lumbar Pain Rehab software. Outcomes were measured at baseline, 4 th week, and 8 th week using the Depression, Anxiety, and Stress Scale (DASS), Pain Catastrophizing Scale (PCS), Coping Strategies Questionnaire (CSQ), Tampa Scale for Kinesiophobia (TSK), and Simulator Sickness Questionnaire (SSQ). The ethical approval was acquired (IRB no.0543; reference no. SMDC-IRB/AI/18–1/2023). The VR group demonstrated significantly better reductions in depression, anxiety, and stress at the 4 th week, alongside improved adaptive coping strategies and decreased pain catastrophizing compared with TE. These advantages were sustained at the 8 th week, with further improvement in kinesiophobia and a continued enhancement of emotional well-being. No adverse VR-related effects were reported. VR-based exercise demonstrated superior benefits over TE in enhancing psychological well-being, reducing fear of movement, and promoting adaptive coping strategies in postpartum women with LPP. ClinicalTrials.gov Identifier: NCT05921747, registered on 4/17/2023.